Speech acts in Royal speech delivered by King Rama VI - Liamprawat, Suwattana (Journal of the Faculty of Arts, Silpakorn University, 2020)
This research aims to studying speech acts in 143 royal speeches delivered by King Rama VI during 2453 – 2467 BE. The results at the study reveal at five speech acts were employed namely 1) assertive 2) directive 3) commissive 4) expressive and 5) declarative. The outstanding speech act is directive speech act. The monarch recommended practical guide to his subjects in time of crisis. This directive speech act enhances the value of his royal speech and it is practical to fellow his direction.